RESEARCHING THE NATURAL MOISTURE OF THE HILLY SOILS OF THE NAMANGAN REGION WITH THE AIM OF DEVELOPING RAIN-FED GARDENING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the results of measurements carried out to determine natural soil moisture in the hilly areas of the Namangan region. The possibilities for the development of rain-fed gardening with the effective use of natural moisture in hilly soils are also analyzed.